Surgical Treatment of Labral Tears: Debridement, Repair, and Reconstruction. Issue 1 (29th March 2021) - Nwachukwu, Benedict; Rasio, Jonathan; Sullivan, Spencer; Okoroha, Kelechi; Mather, Richard C.; Nho, Shane J.
Abstract : Advances in hip preservation surgery have to lead to increased utilization of hip arthroscopy. With this, there has also been a growth in the understanding of various hip conditions, therefore, leading to an increase in hip conditions amenable to arthroscopic intervention. The acetabular hip labrum has been at the forefront of arthroscopic advances in the hip. The labrum is important for hip stability, provision of the suction seal, and joint proprioception. Given the labrum's central role in hip biomechanics, there is increasing emphasis on labral preservation in the form of debridement and repair. In revision settings, advanced techniques such as labral augmentation and reconstruction may play a role in the management of labral pathology. Appropriate management of the hip labrum at the time of surgery can be an important mediator of the outcome. As such, an understanding of the evolving evidence base and surgical indications and techniques are integral to the treatment and management of labral pathology.